2023
DOI: 10.3390/ijms24076374
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Bcl-2 Family Proteins in Tetraploidization-Related Senescence

Abstract: The B-cell lymphoma 2 (Bcl-2) family of proteins is the main regulator of apoptosis. However, multiple emerging evidence has revealed that Bcl-2 family proteins are also involved in cellular senescence. On the one hand, the different expression of these proteins determines the entry into senescence. On the other hand, entry into senescence modulates the expression of these proteins, generally conferring resistance to apoptosis. With some exceptions, senescent cells are characterized by the upregulation of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 119 publications
0
0
0
Order By: Relevance
“…Thirdly, activated ciliogenesis helps to understand the increased resistance of polyploid cells to stress, DNA damage, apoptosis, immune surveillance, and chemotherapeutic drugs [79,91,97,[117][118][119]. It was recently shown that ciliogenesis activates double strand break DNA repair via the NUA4/TIP60 chromatin acetyl transferase complex mentioned above.…”
Section: Polyploidy Promotes Ciliogenesis and The Centrosome Cyclementioning
confidence: 99%
“…Thirdly, activated ciliogenesis helps to understand the increased resistance of polyploid cells to stress, DNA damage, apoptosis, immune surveillance, and chemotherapeutic drugs [79,91,97,[117][118][119]. It was recently shown that ciliogenesis activates double strand break DNA repair via the NUA4/TIP60 chromatin acetyl transferase complex mentioned above.…”
Section: Polyploidy Promotes Ciliogenesis and The Centrosome Cyclementioning
confidence: 99%